Surface Modification of Ti–30Ta Alloy by Deposition of P(VDF-TrFE)/BaTiO3 Coating for Biomedical Applications - Ribeiro, Larissa Mayra Silva; Costa da Rosa Simões, Luziane Aparecida; Espanhol-Soares, Melina; Carvalho Teles, Vinicius; Ribeiro, Tainara Aparecida Nunes; Capellato, Patrícia; Vasconcelos Fré, Lucas Victor Benjamim; Kuffner, Bruna Horta Bastos; Saddow, Stephen Edward; Sachs, Daniela; Rosifini Alves Claro, Ana Paula [UNESP]; Gimenes, Rossano (MDPI, 2022)
This study aims to promote an adequate methodology for coating an experimental Ti-30Ta alloy with P(VDF-TrFE)/BaTiO3. The combination of a copolymer with a ceramic has not been used until now. Ti-30Ta is an excellent choice to replace current alloys in the global market. The composite deposition on the Ti-30Ta substrate was performed by a spray coating process and at low temperature using two different surface modifications: surface acidic etching and surface polishing. Characterization was divided into four areas: (I) the substrate surface treatments used and their influences on the adhesion process were evaluated using surface energy, wettability, and roughness analyses; (II) the properties of the composite film, which were carried out using X-ray diffractometry (XRD), Fourier transform infrared spectroscopy (FTIR), thermogravimetric analysis (TG), and differential scanning calorimetry (DSC); (III) the study of the adhesion of the film on the substrate, which was performed by a scratch test; (IV) the final product, which was evaluated to determine the surface properties after the coating process. Biofilm formation using Staphylococcus aureus and Staphylococcus epidermidis strains and a hemocompatibility test were performed as biological assays. The results indicated that the P(VDF-TrFE)/BaTiO3 film showed high thermal stability (up to ≈450 °C); the FTIR and DSC tests indicated the presence of the β phase, which means that the material presents a piezoelectric nature; and the scratch test showed that the samples with the polish treatment provided a better adhesion of the film with an adhesion strength of ~10 MPa. From the SEM analysis, it was possible to determine that the spray deposition coating process resulted in a well-applied film as evidenced by its homogeneity. Microbiological tests showed that for Staphylococcus aureus, the bacterial growth in the coated Ti-30Ta presented no significant differences when compared to the alloy without coating. However, for Staphylococcus epidermidis, there was considerable growth on the coated Ti-30Ta, when compared to the non-coated alloy, indicating that the film surface may have favored bacterial growth. The hemolysis assay showed that the coated material presents hemocompatible characteristics when in contact with blood cells. The results obtained indicate that the Ti-30Ta alloy coated with P(VDF-TrFE)/BaTiO3 is a promising alternative for implant applications, due to its biocompatible properties, simplicity, and low cost.
Keywords: biofilm adhesion; P(VDF-TrFE)/BaTiO3 composite; spray coating; surface characterization; Ti-30Ta alloy